Effects of Heme Oxygenase-1 Inducer and Inhibitor on Experimental Autoimmune Uveoretinitis - Jang, Jeong Un; Lee, Sook Hee; Choi, Chang Uk; Bahk, Song-Chull; Chung, Hun Taeg; Yang, Yun Sik (Korean journal of ophthalmology, 2007)
Experimental autoimmune uveoretinitis (EAU) is an animal model of posterior uveitis and heme oxygenase-1 (HO-1) is a well-known anti-oxidant factor. However, there is no report a protective role of HO-1 on EAU in vivo. To verify that HO-1 is induced in EAU by interphotoreceptor retinoid-binding protein (IRBP), that an HO-1 inducers ameliorates the associated inflammation, and that an HO-1 inhibitor exacerbates this inflammation. Forty four Lewis rats were given either 40 mol/kg hemin or 40 mol/kg SnPP (tin protoporphyrin IX) by intraperitoneal injection and twenty two uveitis control rats were injected with 0.5 mL of saline once daily 5-20 days after IRBP immunization inducing EAU. Three normal control rats were used for Western blotting and ELISA assay of HO-1. The clinical uveitis signs of inflammation were scored in the three groups from 0 to 4 on alternate three days. To confirm the clinical results, histological and immunohistochemical stain of HO-1 were performed on the day of peak inflammation and Western blotting and ELISA assay of HO-1 were performed on 6th, 12th and 18th day after IRBP immunization. Hemin, an inducer of HO-1, ameliorated the clinical signs of EAU. In contrast, SnPP-treated rats show that the severity of the clinical sign were exacerbated at the peak period of the disease. These results are roughly compatible with histological, immunoblotting, and immunohistochemical evaluations and an ELISA assay of HO-1. We suggest that HO-1 plays an important protective role in EAU.